2004
DOI: 10.1111/j.1442-2042.2004.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation of microvessel density with metastasis and prognosis in renal cell carcinoma

Abstract: Background : Although a correlation between microvessel density (MVD) and tumor aggressiveness has been established for several malignancies, the data for renal cell carcinoma (RCC) is conflicting. In order to clarify the significance of MVD, we investigated the relationships between MVD and tumor stage, grade, size, occurrence of metastasis and patient survival. Methods : Tumor specimens from 70 patients with primary renal cell carcinoma were examined by immunohistochemical staining for CD34.Results : There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 31 publications
5
49
1
1
Order By: Relevance
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 56%
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 56%
“…An interesting observation is that Lim1 silencing in tumors of human CCC-bearing nude mice did not affect tumor vascularization. It should be noted, however, that reports dealing with the prognostic value of vascularisation in human CCC have shown either no effect on patient survival, better survival, or worse prognosis (MacLennan and Bostwick, 1995;Nativ et al, 1998;Imao et al, 2004;Yao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…RCC is a hypervascular tumour for which data on the relationship between tumour vascularity and prognosis are conflicting [1]. Yoshino et al [2] and Paradis et al [3] reported that patient survival was significantly correlated with microvessel density (MVD), while others [4][5][6] reported that MVD did not correlate with metastasis.…”
Section: Introductionmentioning
confidence: 99%